What you have here is a quadratic polynomial.
The form is: ax^2 + bx + c
C is ALWAYS the y-intercept in non-linear polynomials. So we immediately know the y-intercept to be 1.
For the X-intercept(s), we can solve in a few ways, but let's use the quadratic formula.
The quadratic formula states that y=-b+-((sqrt(b^2-4ac) / 2a).
A = 2
B = 3
C = 1
Plug in your information,
![(-3 (+)/(-) √(3^2 - 4(2)(1)) )/(2(2)) \\√(9 - 8)\\ √(1) \\\\(-3 (+)/(-) 1)/(4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5d0p1d00z0b0jepl85g1qwi901fmed6kll.png)
y = (-3 +- 1) / 4
X = -.05
X = -1
Y = 1
X-Intercepts: -.05, -1
Y-Intercepts: 1